Evaluasi Penggunaan Antibiotik menggunakan Metode ATC/DDD di Puskesmas Pamolokan Kabupaten Sumenep Periode Juli-Desember 2024 - Fatimatuz Zahra; Rizdyana Firmaniar; RB. Asyim (CV. ITTC INDONESIA, 2026)
Antibiotics are compounds that are effective in inhibiting the growth of microorganisms. However, misuse of antibiotics is still common in various health care facilities. Various studies show that around 40-62% of antibiotics are used inappropriately, especially for diseases that do not actually require antibiotic therapy. This misuse contributes significantly to the increasing cases of antimicrobial resistance (AMR) infections, which is now one of the serious threats to global health. This study aims to determine and evaluate the pattern of antibiotic use using the Anatomical Therapeutic Chemical/Defined Daily Dose (ATC/DDD) method at the Pamolokan Health Center, Sumenep Regency in the July-December 2024 period. This research is a quantitative descriptive study with a retrospective design. The data used were secondary data in the form of prescription records of adult patients (aged ≥ 17 years) who obtained antibiotics at Pamolokan Health Center during the period, obtained from the pharmaceutical installation. Based on the results of the study, there were four types of antibiotics used in adult outpatients, namely Amoxicillin, Cefadroxil, Clindamycin, and Metronidazole, with Amoxicillin as the most prescribed antibiotic, totaling 5.228 tablets. The results of the evaluation of antibiotic use based on the ATC/DDD method showed that Amoxicillin had the highest DDD/1000 KPRJ value of 200,65 DDD/1000 KPRJ, followed by Clindamycin at 47,78 DDD/1000 KPRJ, Cefadroxil at 35,98 DDD/1000 KPRJ, and Metronidazole at 11,92 DDD/1000 KPRJ.